The Ethics of Determining One's Own Death : Essays on Den Hartogh's What Kind of Death - van Donselaar, Gijs; Rijpkema, Peter; Wijsbek, Henri (Amsterdam University Press, 2025)
This collection brings together key contributions on the ethics of end-of-life decisions, inspired by the publication of What Kind of Death: The Ethics of Determining One's Own Death, a new standard work by professor Govert den Hartogh. The topics covered reflect the book's comprehensive approach, with its central themes explored by ethicists, legal experts, and medical professionals. The various contributions offer a thorough examination of the major steps in Den Hartogh's 'dual track approach'. This collection serves as a valuable supplement to the book and an important contribution to the ongoing debate about patient self-determination and well-being as foundational values in the ethics of determining one's own death.